Micropore Size Analysis of Activated Carbons Using Nitrogen, Carbon Dioxide and Methane Adsorption Isotherms: Experimental and Theoretical Studies - Abbas Aleghafouri; Mohsen Mohsen-Nia; Ali Mohajeri; Mohammad Mahdyarfar; Morteza Asghari (Adsorption Science & Technology)
Nitrogen (N 2 , at 77 K and sub-atmospheric pressure), carbon dioxide (CO 2 , at 273 K, sub-atmospheric pressure and high pressure) and methane (CH 4 , at 298 K and high pressure) adsorption isotherms have been obtained for three microporous-activated carbons in order to characterize their micropore size distributions (MPSDs). A comparison of the results has shown that the shape of the isotherms was different, which was due in part to differences in the overall micropore volume and the MPSDs for the carbon samples studied in this work. According to the results, despite the different characteristics of CO 2 and CH 4 , a quite good consistency between the MPSDs from these two gases was obtained for the three carbon samples. Finally, it was shown that the adsorption isotherms of CO 2 and CH 4 at the higher temperatures should be considered as a complement to N 2 adsorption at 77 K for the characterization of porous texture (micropore volume and MPSDs) of activated carbon samples.